Trajetórias de mulheres no circuito fotográfico de Curitiba (1970 - 1980) - Oliveira, Heloisa Nichele de (2021)
In this research I highlight the role of photographers in the photographic circuit in Curitiba, in the 1970s and 1980s. In the light of research on Women’s History, I aim to reconstruct the trajectories, experiences and sociability of women in photography in the city during this period. For this, in the articulation of the theoretical framework, oral narratives and a diverse set of documentary sources such as newspapers, magazines, photographs and catalogs, I map, describe and analyze events, spaces and networks of sociabilities from which the work of photographers was made gift. In this sense, I understand photography as a social practice located according to the notion of cultural circuit, which touches on individual projects of photographers in the exercise of their profession. For this mapping, I use public and personal files, from physical and digital collections. As a result, I hope to contribute to research that investigates the protagonism of women in photography, based on the argument that looking at these trajectories inserted in a field of situated, contingent and dynamic possibilities, makes it possible to locate the work of photographers in arrangements that overwrite positions social, alliances, disputes, resistances, transits and deviations.